Species distribution and concentration pollution of soil heavy metals in coal mine reclamation areas - Xing, Jie; Gao, Lianfeng; He, Li (Frontiers in Environmental Science, 2022)
In order to understand the distribution characteristics of heavy metal elements in the soil of the coal mine reclamation area and its impact on the surrounding environment, and provide technical support for the selection of a reasonable method for the coal mine land reclamation. Taking the soil of Shanxi coal mine reclamation area as the research object. The distribution characteristics of four heavy metal elements in the soil of two different reclamation methods in deep and shallow coal mines were studied by continuous extraction method. The research results show that The content of heavy metals in the deep reclamation area is significantly higher than that in the unreclaimed area and the content of Zn and Cr is 6.23 times and 1.57 times that of the unreclaimed area; The content of heavy metal Zn is more than 9 times of the national standard value; Soils in deep reclamation areas have been contaminated with Zn and Cr; The heavy metal content in the shallow reclamation area is higher than that in the unreclaimed area, but lower than the national standard value; Pb in the coal mine reclamation area has a high pollution impact on the surrounding soil; Although the content of Zn in the soil is relatively large, due to the stable nature of the residue, it has little impact on the environment. Heavy metals Ni and Cr are dangerous to the surrounding soil under certain conditions; The RSP value of the heavy metal Pb in the soil of the deep and shallow reclamation areas is the largest, which has the greatest impact on the environment, and the other three heavy metals have no pollution. Pb in coal mines has a serious impact on the environment.